Technological evaluation of stones from the eastern region of the state of São Paulo, Brazil, for railway ballast - Daniela Tomaz Alves; Rogério Pinto Ribeiro; Gustavo de Castro Xavier; Sergio N. Monteiro; Afonso R. G. de Azevedo (Scientific Reports)
Abstract The correct choice of a stone aggregate for railway ballast is directly related to the stability, safety, efficiency, and maintenance costs of the track. The aggregate must meet several criteria to ensure it is the most appropriate material. Thus, the present study aimed to evaluate four distinct stones: two granites, a diabase, and a basalt, all mined in the eastern region of the state of São Paulo, Brazil, regarding their applicability as ballast. Using Brazilian and ASTM procedures for stone samples, the tests were conducted on 55 and 75-mm specimens, in dry and wet conditions. As a result, all stones met the physical properties established by the standards. Among the mechanical properties, uniaxial compressive strength stood out, with all stones where the tested materials advantageously exceeding the 100 MPa required by the Brazilian standard. Regarding the accelerated weathering test with ethylene glycol, only basalt showed more significant changes, although its resistance to weathering was still lower than 10%. Our findings indicate that these stones perform adequately as ballast for railway applications. The study is expected to contribute to revisions of technical standards and the improvement of a database on Brazilian stone materials for use as railway ballast.